'Missed' oesophageal adenocarcinoma and high‐grade dysplasia in Barrett's oesophagus patients: A large population‐based study. Issue 4 (1st May 2018) - van Putten, Margreet; Johnston, Brian T; Murray, Liam J; Gavin, Anna T; McManus, Damian T; Bhat, Shivaram; Turkington, Richard C; Coleman, Helen G
Abstract : Background: A systematic review suggests that 25% of oesophageal adenocarcinomas (OAC) are 'missed' at index endoscopy for Barrett's oesophagus (BO); however, this included few population‐based studies and may be an overestimate. Objective: The objective of this article is to quantify the 'missed' rates of high‐grade dysplasia (HGD) and OAC at index BO endoscopy. Methods: Patients from the Northern Ireland BO register diagnosed between 1993 and 2010 ( n = 13, 159) were linked to the Northern Ireland Cancer Registry to identify patients who developed OAC or HGD. Logistic regression analysis compared characteristics of 'missed' vs 'incident' HGD/OAC, defined as diagnoses within 3–12 months vs >1 year after incident BO, respectively. Results: A total of 267 patients were diagnosed with HGD/OAC ≥3 months after BO diagnosis, of whom 34 (12.7%) were potentially 'missed'. The proportion of 'missed' HGD/OAC was 25% among BO patients with low‐grade dysplasia (LGD) and 9% among non‐dysplastic BO patients. Older age and BO‐LGD carried a higher risk of 'missed' HGD/OAC. Non‐dysplastic BO patients were more often diagnosed with a 'missed' OAC (rather than HGD; 89%), compared with BO‐LGD patients (40%). Conclusions: Approximately one in 10 HGD/OAC cases are 'missed' at incident BO diagnosis, which is significant but lower than previous reports. However, 'missed' HGD/OAC cases represent only 0.26% of all BO patients.